Disaster Risk Finance for Adaptive Social Protection - Cubas, Diana (World Bank, Washington, DC, 2020)
Countries in the Latin America and the Caribbean (LAC) region are highly exposed to frequent natural hazards leading to disasters. Usually, poor and vulnerable populations are adversely affected by the effects of disasters since they have less ability to cope and recover. Rapid assistance in the immediate aftermath of a disaster is an essential part of strengthening resilience and protecting the welfare of poor and vulnerable households. If ex-ante physical and financial measures are not included in disaster preparedness, there can be considerable delays in post-disaster response, potentially significantly exacerbating the adverse human and economic conditions of the poor and vulnerable, pushing them deeper into poverty. Social Protection (SP) has an important role in helping the poor and vulnerable populations cope with the impacts of natural hazards as well as building long-term resilience. Ensuring the availability of financing to scale-up Social Protection after disasters is therefore critically important for LAC countries. LAC countries have demonstrated experiences using various risk financing approaches and participating in risk financing arrangements. Despite this, few countries have established mechanisms to guarantee scaled-up SP support following disaster events. This note aims to improve understanding of Disaster Risk Financing (DRF) approaches among SP practitioners and outlines what LAC countries need to prioritize in order to ensure that appropriate financing arrangements are in place to support effective post-disaster SP response.